High-gelation-activity geopolymer based on copper smelting slag as well as preparation method and application of high-gelation-activity geopolymer
By preparing highly gelled active geopolymers based on copper smelting slag, the problems of low utilization rate of copper smelting slag and environmental pollution are solved, and efficient resource utilization and excellent performance of geopolymer materials are achieved.
Patent Information
- Application Number
- CN202411714319.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-04-11
AI Technical Summary
The utilization rate of copper smelting slag is low and is mainly used to manufacture low-value-added building materials, resulting in waste of resources and environmental pollution.
By preparing highly gelled active geopolymers based on copper smelting slag, using a combination of copper smelting slag, exciter, water and additives, and through wet stirring and molding and maintenance processes, a geopolymer material with excellent mechanical properties and stability is produced.
It has achieved efficient resource utilization of copper smelting slag and produced geopolymer materials with excellent performance, which not only solved the environmental pollution problem, but also reduced production costs, and has broad application prospects.
Smart Images

Figure BDA0005156552320000091 
Figure BDA0005156552320000101
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of copper smelting slag recycling, and in particular to a high-gelling active geopolymer based on copper smelting slag, a preparation method and an application thereof. Background Art
[0002] Geopolymer materials are a new type of inorganic polymer materials with excellent mechanical properties and durability. They are widely used in building materials, road engineering, environmental protection engineering and other fields. Traditional geopolymer materials are mainly prepared from industrial wastes such as slag and fly ash, and form a three-dimensional network structure with high strength and stability through the action of alkaline activators. However, with the development of industrial production, the supply of slag and fly ash has gradually decreased, and finding new raw materials to prepare geopolymers has become a research hotspot.
[0003] Copper smelting slag is a large amount of waste generated during the copper smelting process. Its main components are silicon dioxide, aluminum oxide, iron oxide, etc. A large amount of copper smelting slag is produced every year in the world. If these wastes are not properly handled, they will not only occupy a large amount of land resources, but also cause serious pollution to the environment. At present, the utilization rate of copper smelting slag is low, and it is mainly used to manufacture low-value-added products such as cement and building materials. Therefore, the resource utilization and recycling of copper smelting slag, especially its application in high-value-added products, has become an urgent problem to be solved. Summary of the invention
[0004] In order to solve at least one of the above technical problems, a method for solving the environmental pollution problem of copper smelting slag and producing a geopolymer material with excellent performance is developed. The present application provides a high gelling activity geopolymer based on copper smelting slag, a preparation method and an application.
[0005] In one aspect, the present application provides a high gelling activity geopolymer based on copper smelting slag, comprising the following components:
[0006] Copper smelting slag 40-60wt%;
[0007] Activator 15-35wt%;
[0008] Water 10~20wt%;
[0009] Additives 1~5wt%.
[0010] Optionally, the copper smelting slag has a particle size of 0.1 to 1 mm.
[0011] Optionally, the weight ratio of the activator to the copper smelting slag is 0.43-0.70:1.
[0012] Optionally, the activator is one or a combination of sodium silicate and sodium hydroxide;
[0013] Optionally, the activator is a combination of sodium silicate and sodium hydroxide, and the weight ratio of sodium silicate to sodium hydroxide is 1.8 to 2.2:1.
[0014] In a second aspect, the present application provides a method for preparing the above-mentioned geopolymer, comprising the following steps:
[0015] S1. Copper smelting slag treatment
[0016] The copper smelting slag is crushed and screened to remove large particles and impurities, and the copper smelting slag with a particle size of 0.1 to 1 mm is screened out;
[0017] S2. Preparation of activator
[0018] Dissolving the stimulant in water according to the formula amount to prepare an stimulant solution;
[0019] S3, mixed reaction
[0020] The copper smelting slag prepared in S1 and the activator solution prepared in S2 are mixed according to a certain proportion, and stirred for 40 to 80 minutes to obtain a slurry;
[0021] S4, Forming
[0022] The slurry prepared in S3 is injected into a mold, and after vibrating and exhausting, a molding process is performed to obtain a geopolymer material;
[0023] S5. Post-maintenance
[0024] The formed geopolymer material is cured to obtain a high gelling activity geopolymer based on copper smelting slag.
[0025] Optionally, in S5, the curing method is: curing at 80° C. and 80% humidity for 24 hours.
[0026] In a third aspect, the present application provides applications of the above-mentioned geopolymer in the fields of building materials and environmental protection technology.
[0027] In summary, the present application includes at least one of the following beneficial technical effects:
[0028] 1. By adjusting the addition amount of copper smelting slag, sodium silicate, sodium hydroxide and other additives, the high gelling activity of copper smelting slag is stimulated, and the obtained geopolymer material has excellent mechanical properties and stability;
[0029] 2. Use wet mixing and molding curing technology to ensure uniform geopolymer materials and stable performance;
[0030] 3. Converting industrial waste copper smelting slag into geopolymer material products with high added value not only protects the environment but also reduces production costs. It has broad application prospects and significant economic benefits. DETAILED DESCRIPTION
[0031] The present application is further described in detail below with reference to the embodiments.
[0032] In the following examples of the present application, the main components involved, unless otherwise specified, were purchased from commercially available products.
[0033] The copper smelting slag comes from Tongling Nonferrous Metals Group.
[0034] The additive is exemplified by limestone powder, the main component of which is calcium carbonate, which comes from Tongling Nonferrous Metals Group. Specific embodiments
[0036] Example 1
[0037] This embodiment is used to prepare a high gelling active geopolymer based on copper smelting slag, and the details are as follows.
[0038] The copper smelting slag is crushed and screened to remove large particles and impurities, and the copper smelting slag with a particle size of 0.1 to 1 mm is screened out;
[0039] Dissolve 21.00 kg of sodium silicate and 14.00 kg of sodium hydroxide in 20 kg of water to prepare an alkaline activator solution;
[0040] 40.00 kg of copper smelting slag was mixed with the activator solution and stirred for 60 minutes to obtain a slurry.
[0041] The prepared slurry is injected into a mold, and after vibrating and exhausting, a molding process is performed to obtain a geopolymer material;
[0042] The formed geopolymer material is cured at 80° C. and 80% humidity for 24 hours to obtain a high gelling active geopolymer based on copper smelting slag.
[0043] Example 2
[0044] This embodiment is used to prepare a high gelling active geopolymer based on copper smelting slag, and the details are as follows.
[0045] The copper smelting slag is crushed and screened to remove large particles and impurities, and the copper smelting slag with a particle size of 0.1 to 1 mm is screened out;
[0046] Dissolve 22.15 kg of sodium silicate and 13.85 kg of sodium hydroxide in 19 kg of water to prepare an alkaline activator solution;
[0047] 42.00 kg of copper smelting slag was mixed with the activator solution and stirred for 60 minutes to obtain slurry.
[0048] The prepared slurry is injected into a mold, and after vibrating and exhausting, a molding process is performed to obtain a geopolymer material;
[0049] The formed geopolymer material is cured at 80° C. and 80% humidity for 24 hours to obtain a high gelling active geopolymer based on copper smelting slag.
[0050] Example 3
[0051] This embodiment is used to prepare a high gelling active geopolymer based on copper smelting slag, and the details are as follows.
[0052] The copper smelting slag is crushed and screened to remove large particles and impurities, and the copper smelting slag with a particle size of 0.1 to 1 mm is screened out;
[0053] Dissolve 20.78 kg of sodium silicate and 12.22 kg of sodium hydroxide in 18 kg of water to prepare an alkaline activator solution;
[0054] 44.00 kg of copper smelting slag was mixed with the activator solution and stirred for 60 minutes to obtain a slurry.
[0055] The prepared slurry is injected into a mold, and after vibrating and exhausting, a molding process is performed to obtain a geopolymer material;
[0056] The formed geopolymer material is cured at 80° C. and 80% humidity for 24 hours to obtain a high gelling active geopolymer based on copper smelting slag.
[0057] Example 4
[0058] This embodiment is used to prepare a high gelling active geopolymer based on copper smelting slag, and the details are as follows.
[0059] The copper smelting slag is crushed and screened to remove large particles and impurities, and the copper smelting slag with a particle size of 0.1 to 1 mm is screened out;
[0060] Dissolve 23.14 kg of sodium silicate and 12.86 kg of sodium hydroxide in 17 kg of water to prepare an alkaline activator solution;
[0061] 46.00 kg of copper smelting slag was mixed with the activator solution and stirred for 60 minutes to obtain slurry.
[0062] The prepared slurry is injected into a mold, and after vibrating and exhausting, a molding process is performed to obtain a geopolymer material;
[0063] The formed geopolymer material is cured at 80° C. and 80% humidity for 24 hours to obtain a high gelling active geopolymer based on copper smelting slag.
[0064] Example 5
[0065] This embodiment is used to prepare a high gelling active geopolymer based on copper smelting slag, and the details are as follows.
[0066] The copper smelting slag is crushed and screened to remove large particles and impurities, and the copper smelting slag with a particle size of 0.1 to 1 mm is screened out;
[0067] Dissolve 21.62 kg of sodium silicate and 11.38 kg of sodium hydroxide in 16 kg of water to prepare an alkaline activator solution;
[0068] 48.00 kg of copper smelting slag was mixed with the activator solution and stirred for 60 minutes to obtain a slurry.
[0069] The prepared slurry is injected into a mold, and after vibrating and exhausting, a molding process is performed to obtain a geopolymer material;
[0070] The formed geopolymer material is cured at 80° C. and 80% humidity for 24 hours to obtain a high gelling active geopolymer based on copper smelting slag.
[0071] Example 6
[0072] This embodiment is used to prepare a high gelling active geopolymer based on copper smelting slag, and the details are as follows.
[0073] The copper smelting slag is crushed and screened to remove large particles and impurities, and the copper smelting slag with a particle size of 0.1 to 1 mm is screened out;
[0074] Dissolve 23.33 kg of sodium silicate and 11.67 kg of sodium hydroxide in 10 kg of water to prepare an alkaline activator solution;
[0075] 50.00 kg of copper smelting slag was mixed with the activator solution and stirred for 60 minutes to obtain slurry.
[0076] The prepared slurry is injected into a mold, and after vibrating and exhausting, a molding process is performed to obtain a geopolymer material;
[0077] The formed geopolymer material is cured at 80° C. and 80% humidity for 24 hours to obtain a high gelling active geopolymer based on copper smelting slag.
[0078] Example 7
[0079] This embodiment is used to prepare a high gelling active geopolymer based on copper smelting slag, and the details are as follows.
[0080] The copper smelting slag is crushed and screened to remove large particles and impurities, and the copper smelting slag with a particle size of 0.1 to 1 mm is screened out;
[0081] Dissolve 23.71 kg of sodium silicate and 11.29 kg of sodium hydroxide in 10 kg of water to prepare an alkaline activator solution;
[0082] 52.00 kg of copper smelting slag was mixed with the activator solution and stirred for 60 minutes to obtain slurry.
[0083] The prepared slurry is injected into a mold, and after vibrating and exhausting, a molding process is performed to obtain a geopolymer material;
[0084] The formed geopolymer material is cured at 80° C. and 80% humidity for 24 hours to obtain a high gelling active geopolymer based on copper smelting slag.
[0085] Example 8
[0086] This embodiment is used to prepare a high gelling active geopolymer based on copper smelting slag, and the details are as follows.
[0087] The copper smelting slag is crushed and screened to remove large particles and impurities, and the copper smelting slag with a particle size of 0.1 to 1 mm is screened out;
[0088] Dissolve 21.31 kg of sodium silicate and 9.69 kg of sodium hydroxide in 12 kg of water to prepare an alkaline activator solution;
[0089] 54.00 kg of copper smelting slag was mixed with the activator solution and stirred for 60 minutes to obtain slurry.
[0090] The prepared slurry is injected into a mold, and after vibrating and exhausting, a molding process is performed to obtain a geopolymer material;
[0091] The formed geopolymer material is cured at 80° C. and 80% humidity for 24 hours to obtain a high gelling active geopolymer based on copper smelting slag.
[0092] Example 9
[0093] This embodiment is used to prepare a high gelling active geopolymer based on copper smelting slag, and the details are as follows.
[0094] The copper smelting slag is crushed and screened to remove large particles and impurities, and the copper smelting slag with a particle size of 0.1 to 1 mm is screened out;
[0095] Dissolve 16.73 kg of sodium silicate and 7.27 kg of sodium hydroxide in 15 kg of water to prepare an alkaline activator solution;
[0096] 56.00 kg of copper smelting slag was mixed with the activator solution and stirred for 60 minutes to obtain slurry.
[0097] The prepared slurry is injected into a mold, and after vibrating and exhausting, a molding process is performed to obtain a geopolymer material;
[0098] The formed geopolymer material is cured at 80° C. and 80% humidity for 24 hours to obtain a high gelling active geopolymer based on copper smelting slag.
[0099] Example 10
[0100] This embodiment is used to prepare a high gelling active geopolymer based on copper smelting slag, and the details are as follows.
[0101] The copper smelting slag is crushed and screened to remove large particles and impurities, and the copper smelting slag with a particle size of 0.1 to 1 mm is screened out;
[0102] Dissolve 14.82 kg of sodium silicate and 6.18 kg of sodium hydroxide in 18 kg of water to prepare an alkaline activator solution;
[0103] 58.00 kg of copper smelting slag was mixed with the activator solution and stirred for 60 minutes to obtain slurry.
[0104] The prepared slurry is injected into a mold, and after vibrating and exhausting, a molding process is performed to obtain a geopolymer material;
[0105] The formed geopolymer material is cured at 80° C. and 80% humidity for 24 hours to obtain a high gelling active geopolymer based on copper smelting slag.
[0106] Embodiment 11
[0107] This embodiment is used to prepare a high gelling active geopolymer based on copper smelting slag, and the details are as follows.
[0108] The copper smelting slag is crushed and screened to remove large particles and impurities, and the copper smelting slag with a particle size of 0.1 to 1 mm is screened out;
[0109] Dissolve 10.71 kg of sodium silicate and 4.29 kg of sodium hydroxide in 20 kg of water to prepare an alkaline activator solution;
[0110] 60.00 kg of copper smelting slag was mixed with the activator solution and stirred for 60 minutes to obtain slurry.
[0111] The prepared slurry is injected into a mold, and after vibrating and exhausting, a molding process is performed to obtain a geopolymer material;
[0112] The formed geopolymer material is cured at 80° C. and 80% humidity for 24 hours to obtain a high gelling active geopolymer based on copper smelting slag.
[0113] With reference to GB / T50081-2019, the performance of the high gelling active geopolymer based on copper smelting slag prepared in the above Examples 1 to 11 was tested, and the results are shown in Table 1; wherein: A is the weight ratio of the activator to the copper smelting slag; B is the weight ratio of sodium silicate to sodium hydroxide; C is the improvement rate of the 28d compressive strength relative to the 7d compressive strength.
[0114] Table 1
[0115]
[0116]
[0117] It can be seen from Examples 1 to 11 of the present application and Table 1 that the high gelling active geopolymer based on copper smelting slag prepared in the present application can achieve a 7d compressive strength of more than 27 MPa, and a 28d compressive strength of more than 28 MPa.
[0118] And through further analysis of the data in Table 1, it can be obtained that when the weight ratio of the activator to the copper smelting slag is in the range of 0.43 to 0.70:1, the 7d compressive strength of the prepared high-gelling active geopolymer based on copper smelting slag is relatively high, reaching more than 30 MPa.
[0119] When the weight ratio of sodium silicate to sodium hydroxide is in the range of 1.8 to 2.2:1, the 28d compressive strength of the prepared high-gelling active geopolymer based on copper smelting slag is improved to a greater extent than the 7d compressive strength, which can reach more than 10%.
[0120] Therefore, it can be concluded that in the technical solution of the present application, when the weight ratio of the activator to the copper smelting slag is in the range of 0.43 to 0.70:1, the high gelling active geopolymer based on the copper smelting slag prepared has a high initial compressive strength; when the weight ratio of sodium silicate to sodium hydroxide is in the range of 1.8 to 2.2:1, the high gelling active geopolymer based on the copper smelting slag prepared has a high degree of compressive strength improvement over time. Therefore, the weight ratio of the activator to the copper smelting slag and the weight ratio of sodium silicate to sodium hydroxide in the technical solution of the present application can be adjusted according to the application field of the geopolymer.
[0121] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A highly gelling active geopolymer based on copper smelting slag, characterized in that: Includes the following components: Copper smelting slag 40-60wt%; Activator 15-35wt%; Water 10~20wt%; Additives 1~5wt%.
2. The geopolymer according to claim 1, characterized in that: The particle size of the copper smelting slag is 0.1-1 mm.
3. The geopolymer according to claim 1, characterized in that: The weight ratio of the activator to the copper smelting slag is 0.43-0.70:
1.
4. The geopolymer according to claim 1, characterized in that: The activator is one or a combination of sodium silicate and sodium hydroxide; 5. The geopolymer according to claim 1, characterized in that: The activator is a combination of sodium silicate and sodium hydroxide, and the weight ratio of sodium silicate to sodium hydroxide is 1.8-2.2:
1.
6. A method for preparing the geopolymer according to claim 1, characterized in that: The following steps are involved: S1. Copper smelting slag treatment The copper smelting slag is crushed and screened to remove large particles and impurities, and the copper smelting slag with a particle size of 0.1 to 1 mm is screened out; S2. Preparation of activator Dissolving the stimulant in water according to the formula amount to prepare an stimulant solution; S3, mixed reaction The copper smelting slag prepared in S1 and the activator solution prepared in S2 are mixed according to a certain proportion, and stirred for 40 to 80 minutes to obtain a slurry; S4, Forming The slurry prepared in S3 is injected into a mold, and after vibrating and exhausting, a molding process is performed to obtain a geopolymer material; S5. Post-maintenance The formed geopolymer material is cured to obtain a high gelling activity geopolymer based on copper smelting slag.
7. The preparation method according to claim 6, characterized in that: In the above S5, the curing method is: curing at 80° C. and 80% humidity for 24 hours.
8. Use of the geopolymer according to claim 1 in the field of building materials and environmental protection technology.